The Interaction of Oxidative Stress Response with Cytokines in the Thyrotoxic Rat: Is There a Link? - Balahan Makay; Ozer Makay; Cigdem Yenisey; Gokhan Icoz; Gokhan Ozgen; Erbil Unsal; Mahir Akyildiz; Enis Yetkin (Mediators of Inflammation)
Oxidative stress is regarded as a pathogenic factor in hyperthyroidism. Our purpose was to determine the relationship between the oxidative stress and the inflammatory cytokines and to investigate how melatonin affects oxidative damage and cytokine response in thyrotoxic rats. Twenty-one rats were divided into three groups. Group A served as negative controls. Group B had untreated thyrotoxicosis, and Group C received melatonin. Serum malondialdehyde (MDA), glutathione (GSH), glutathione reductase (GR), glutathione peroxidase (GPx), and nitric oxide derivates (NO•x), and plasma IL-6, IL-10, and TNF-alpha were measured. MDA, GSH, NO•x, IL-10, and TNF-alpha levels increased after L-thyroxine induction. An inhibition of triiodothyronine and thyroxine was detected, as a result of melatonin administration. MDA, GSH, and NO•x levels were also affected by melatonin. Lowest TNF-alpha levels were observed in Group C. This study demonstrates that oxidative stress is related to cytokine response in the thyrotoxic rat. Melatonin treatment suppresses the hyperthyroidism-induced oxidative damage as well as TNF-alpha response.